2015
DOI: 10.1308/003588415x14181254789367
|View full text |Cite
|
Sign up to set email alerts
|

Experience of managing open fractures of the lower limb at a major trauma centre

Abstract: INTRODUCTION In April 2012 the John Radcliffe Hospital in Oxford became a major trauma centre (MTC). The British Orthopaedic Association and British Association of Plastic, Reconstructive and Aesthetic Surgeons joint standards for the management of open fractures of the lower limb (BOAST 4) require system-wide changes in referral practice that may be facilitated by the MTC and its associated major trauma network. METHODS From 2008 to 2013 a multistep audit of compliance with BOAST 4 was conducted to assess ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…The lesions of the types III of Gustilo prevailed in our series. In the study reported by AM Ali et al, the lesions of the type IIIa, IIIb and IIIc accounted for 8%, 76% and 16% respectively [11]. With regard to the lesions of the type III, our results correspond to those of Frederico Carlos et al [10] which also noted a predominance of type IIIa Lesions.…”
Section: Discussionsupporting
confidence: 85%
“…The lesions of the types III of Gustilo prevailed in our series. In the study reported by AM Ali et al, the lesions of the type IIIa, IIIb and IIIc accounted for 8%, 76% and 16% respectively [11]. With regard to the lesions of the type III, our results correspond to those of Frederico Carlos et al [10] which also noted a predominance of type IIIa Lesions.…”
Section: Discussionsupporting
confidence: 85%
“…In common with other studies, we have shown support for an orthoplastics service following the introduction of the trauma network. [12][13][14][15][16][17][18][19] Plastic surgical involvement is an integral factor in major trauma service planning and provision from postgraduate training to the provision of joint orthoplastics operating lists. The reduction we identified in the number of patients undergoing skeletal stabilisation and who later underwent soft-tissue coverage suggests a coordinated orthoplastic service.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, the BOAST 4 Standards were published which emphasized the importance of early transfer of patients with complex open lower limb fractures to a specialist centre [15]. In 2012, major trauma centres (MTC) and associated major trauma networks were created to improve patient transfer in the UK [911]. The major goal was reducing complications such as osteomyelitis by means of soft-tissue coverage within 72 h of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported successful results of major trauma centres (MTC) in the United Kingdom following these standards. A decrease in treatment time, fewer required surgeries per patient, and a higher successful limb reconstruction rate have led to a decrease in deep infection rate [911].…”
Section: Introductionmentioning
confidence: 99%